Optimizing Non-Thermal Magnetic Field to Minimize Weight Loss and Tissue Degradation: Identifying Possible Enzyme Inhibition Mechanisms - Chao-Kai Chang; Prakoso Adi; Rizka Mulyani; Chun-Fu Lin; Ratna Sari Listyaningrum; Shella Permatasari Santoso; Mohsen Gavahian; Chang-Wei Hsieh (Foods)
This research investigates potential mechanisms of novel magnetic field (MF) treatments in inhibiting cell-wall-degrading enzymes, aiming to reduce weight loss and preserve the post-harvest quality of tomatoes (Solanum lycopersicum L.) as a climacteric fruit. The optimization of the processing parameters, including MF intensity (1, 2, 3 mT), frequency (0, 50, 100 Hz), and duration (10, 20, 30 min), was accomplished by applying an orthogonal array design. In particular, the investigation delved into the underlying mechanisms by which MF impedes the activity of tissue-degrading enzymes, such as pectin esterase (PE), polygalacturonase (PG), and cellulase (Cx), during the storage period. The results showed that MF treatment delayed the increase in soluble solids by 1.5 times and reduced titratable acidity by 1.2 times. The optimal treatment conditions—2 mT, 50 Hz, and 10 min—achieved the most significant inhibition of weight loss (4.22%) and maintained tissue integrity for up to 21 days. Optimized MF significantly suppressed enzyme activity, with PE activity reduced by 1.5 times, PG by 2.8 times, and Cx by 2.5 times. Also, cross-sectional images and external appearance demonstrated that MF-treated tomatoes retained their internal tissue structure throughout the extended storage period. These findings suggest that MF treatments can effectively suppress the key enzymes responsible for tissue degradation, ultimately delaying weight loss and softening, preserving post-harvest quality, and contributing to sustainable food production and zero waste.